Exploring the range of impacts of helium in the spectra of double detonation models for Type Ia supernovae - Callan, Fionntan P.; Collins, C E; Sim, S A; Shingles, L J; Pakmor, R; Srivastav, S; Pollin, J M; Gronow, S; Röpke, Friedrich; Seitenzahl, I R (Monthly notices of the Royal Astronomical Society, 2025)
Models of sub-Chandrasekhar mass double detonations for Type Ia supernovae (SNe Ia) suggest a distinguishing property of this scenario is unburnt helium in the outer ejecta. However, modern explosion simulations suggest there may be significant variations in its mass and velocity distribution. We recently presented a NLTE (non local thermodynamic equilibrium) radiative transfer simulation for one realization of the double detonation scenario with a modest He mass (0.018 $M_\odot$) present in the ejecta at relatively high velocities (${\sim }18\,000\, km\, s^{-1}$). That simulation predicted a He i 10 830 Å feature blueward of Mg ii 10 927 Å consistent with near-infrared observations of ‘transitional’ SNe Ia. To demonstrate the expected diversity in the helium signature, here we present a calculation for a double detonation model with a higher He mass (${\sim }$0.04 $M_\odot$) ejected at lower velocities (${\sim }13\,000\, km\, s^{-1}$). Despite our simulation predicting no clear optical or 2 $\m helium features, a strong and persistent He i 10 830 Å absorption is present. The feature appears at wavelengths consistent with the extended blue wing of the Mg ii 10 927 Å feature sometimes present in observations, suggesting this is a helium spectral signature (although for this particular model it is too strong and persistent to be consistent with normal SNe Ia). The significant differences in He i 10 830 Å predicted by the two simulations suggest helium spectral signatures likely show significant variation throughout the SNe Ia population. This motivates further work to use this observable signature to test the parameter space for double detonation models.
Veröffentlicht: 03. April 2025
Gesehen am 02.10.2025